2021
DOI: 10.1186/s12915-021-01113-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and morphological analysis of the developing nemertean brain indicates convergent evolution of complex brains in Spiralia

Abstract: Background The brain anatomy in the clade Spiralia can vary from simple, commissural brains (e.g., gastrotrichs, rotifers) to rather complex, partitioned structures (e.g., in cephalopods and annelids). How often and in which lineages complex brains evolved still remains unclear. Nemerteans are a clade of worm-like spiralians, which possess a complex central nervous system (CNS) with a prominent brain, and elaborated chemosensory and neuroglandular cerebral organs, which have been previously sug… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 127 publications
(171 reference statements)
0
6
2
Order By: Relevance
“…Conversely, anteriorly regenerating worms lack most of the anterior structures and therefore the genes herein expressed may explain the high number of downregulated genes in this regeneration condition, and thus it would be reasonable to find several anterior identities and head markers downregulated in this condition. However, we have found no differential expression of several anterior neural markers previously reported in adult and larval annelids and other invertebrates as aristaless-related homeobox, dachshund, empty spiracles homeobox, forebrain zinc-finger, orthopedia, paired box 3/6, retinal homeobox, six 3/6 homeobox, or synaptotagmin 1 (Gąsiorowski et al, 2021;Kerbl et al, 2016;Santagata et al, 2012).…”
Section: Gene Expression Patterns During Anterior Regeneration and As...contrasting
confidence: 79%
See 2 more Smart Citations
“…Conversely, anteriorly regenerating worms lack most of the anterior structures and therefore the genes herein expressed may explain the high number of downregulated genes in this regeneration condition, and thus it would be reasonable to find several anterior identities and head markers downregulated in this condition. However, we have found no differential expression of several anterior neural markers previously reported in adult and larval annelids and other invertebrates as aristaless-related homeobox, dachshund, empty spiracles homeobox, forebrain zinc-finger, orthopedia, paired box 3/6, retinal homeobox, six 3/6 homeobox, or synaptotagmin 1 (Gąsiorowski et al, 2021;Kerbl et al, 2016;Santagata et al, 2012).…”
Section: Gene Expression Patterns During Anterior Regeneration and As...contrasting
confidence: 79%
“…However, none of the genes previously reported (Gąsiorowski et al, 2021;Kerbl et al, 2016;Santagata et al, 2012) has been found to be significantly differentially expressed in this condition.…”
Section: Gene Expression Patterns and Functional Enrichment During An...contrasting
confidence: 55%
See 1 more Smart Citation
“…As with all nemerteans, Lineus ruber have an eversible proboscis used to catch prey [64]. Lineus ruber's nervous system is formed by a brain and two lateral and dorsal nerve cords, as well as cephalic nerves that emerge from the brain and extend to the anterior area of the head, innervating the frontal sensory organ and eyes [64][65][66][67]. Furthermore, this species possesses a closed circulatory system that consists of two lateral and dorsal blood vessels that run parallel to the lateral and the dorsal nerve cords [64].…”
Section: Genes With Putative Immune Functions Are Expressed In a Vari...mentioning
confidence: 99%
“…As all nemerteans, Lineus ruber have an eversible proboscis used to catch prey (59). Lineus ruber nervous system is formed by a brain and two lateral and a dorsal nerve cords, as well as cephalic nerves that emerge from the brain and extend to the anterior area of the head, innervating the frontal sensory organ and eyes (59)(60)(61)(62). Furthermore, this species possesses a closed circulatory system that consists of two lateral and a dorsal blood vessels that run parallel to the lateral and the dorsal nerve cords (59).…”
Section: Genes With Putative Immune Functions Are Expressed In a Vari...mentioning
confidence: 99%